High diversity of multidrug-resistant Mycobacterium tuberculosis Central Asian Strain isolates in Nepal. (October 2017) - Shah, Yogendra; Maharjan, Bhagwan; Thapa, Jeewan; Poudel, Ajay; Diab, Hassan Mahmoud; Pandey, Basu Dev; Solo, Eddie S.; Isoda, Norikazu; Suzuki, Yasuhiko; Nakajima, Chie
Highlights: Genetic diversity of multidrug-resistant (MDR) Mycobacterium tuberculosis Central Asian Strain isolates was high in Nepal. The transmission of MDR M. tuberculosis was suggested by a clustering analysis using spoligotyping and mycobacterial interspersed repetitive units-variable number of tandem repeat analysis. Rare mutations in the rpoB rifampicin resistance determining region could be used as a marker of MDR M. tuberculosis transmission cases. Abstract: Objectives: Tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB) poses a major public health problem in Nepal. Although it has been reported as one of the dominant genotypes of MTB in Nepal, little information on the Central Asian Strain (CAS) family is available, especially isolates related to multidrug resistance (MDR) cases. This study aimed to elucidate the genetic and epidemiological characteristics of MDR CAS isolates in Nepal. Methods: A total of 145 MDR CAS isolates collected in Nepal from 2008 to 2013 were characterized by spoligotyping, mycobacterial interspersed repetitive unit–variable number tandem repeat (MIRU-VNTR) analysis, and drug resistance-associated gene sequencing. Results: Spoligotyping analysis showed CAS1_Delhi SIT26 as predominant (60/145, 41.4%). However, by combining spoligotyping and MIRU-VNTR typing, it was possible to successfully discriminate all 145 isolates into 116 different types including 18 clusters with 47 isolates (clustering rate 32.4%). About a half of these clustered isolates shared the same genetic and geographical characteristics with other isolates in each cluster, and some of them shared rare point mutations in rpoB that are thought to be associated with rifampicin resistance. Conclusions: Although the data obtained show little evidence that large outbreaks of MDR-TB caused by the CAS family have occurred in Nepal, they strongly suggest several MDR-MTB transmission cases.